Chinese Torreya grandis cv. Merrillii seed oil affects obesity through accumulation of sciadonic acid and altering the composition of gut microbiota - Huan Wang; Ye Li; Rui Wang; Huaifei Ji; Chenyang Lu; Xiurong Su (Food Science and Human Wellness)
Torreya grandis cv. Merrillii (Taxace, Torreya) is mainly distributed across the hilly areas of subtropical China and is well known for its nutritional value. In this study, the ameliorative effects of T. grandis seed oil on lipid metabolism were investigated, and the underlying mechanism was explored from the perspective of gut microbiota. Mice experiments showed that the rate of body mass gain in the group where the mice were fed a high-fat diet (HFD) and supplemented with 550 mg/(kg·day) T. grandis seed oil (HFD + TO550 group) was 42.27%, while it was 62.25% in the HFD group. Compared with the HFD group, the liver and fat indices, total cholesterol, triglycerides, and low-density lipoprotein cholesterol were reduced in the oil-supplement groups. Moreover, the oil supplement significantly changed the fatty acid composition and alleviated pathological damage to the liver caused by the high-fat diet. Additionally, the distinct clustering of bacteria in the composition of gut microbiota was observed in the oil treatment group compared with that in the HFD group. T. grandis seed oil significantly increased the abundance of the beneficial bacteria and short-chain fatty acid producers, including Lactobacillus, Bifidobacterium, Faecalibaculum and Allobaculum. Our results suggest that the supplements of T. grandis seed oil could alleviate hyperlipidemia caused by HFD. These positive effects are considered to be related with sciadonic acid (SCA) and are partially mediated by alterations in gut microbiota composition and functionality.